Revise psychology for AS level - Brody, Roz.; Dwyer, Diana (Hove : Psychology, 2002)
This revision guide is written for all students taking the AQA-A AS psychology exam. It gives guidance on not only how to pass the exam, but also on how to avoid the panic and pitfalls that so many students face when taking exams.
Keywords: Psychology -- Examinations -- Study guides; Psychology